Smarter policies for enhanced food security and food system outcomes - McDermott, John; Allison-Reumann, Laura (International Food Policy Research Institute, 2022)
The COVID-19 pandemic has emphasized a multitude of development challenges and opportunities, some of which are new and some ongoing. The disruptions caused by the pandemic have highlighted the interconnections among almost all aspects of society, including the important linkages between food systems and other sectors that are sometimes separately governed and managed. Achieving the desired food system outcomes of health, sustainability, inclusion, resilience, and efficiency (IFPRI 2021) will require alignment and coordination with other sectors such as health, industry, and social development.